Continuous Monitoring of Turbidity and Conductivity in Wastewater Networks: An Easy Tool to Assess the Pollution Load discharged into receiving water - Bersinger, Thomas; Le Hécho, Isabelle; Bareille, Gilles; Pigot, Thierry; Lecomte, Alexandre (Revue des sciences de l’eau / Journal of Water Science, 2015)
Continuous monitoring of the sanitation network of the urban catchment of Pau (southwest France) has been performed since March 2012 using rain gauges, flowmeters, as well as turbidity and conductivity probes. Good correlations were obtained between turbidity, total suspended solids (TSS) and chemical oxygen demand (COD) on the one hand, and conductivity and total nitrogen on the other hand. This allowed an instantaneous and continuous estimation of pollutant concentrations and fluxes since that date. In the present paper we focused on the results of October 2012, which was characterized by alternating periods of dry and rainy events. Turbidity and conductivity raw data show different trends during the study period depending on the parameter and the rain events. A turbidity peak is observed at the beginning of each rain event but its amplitude varies with the intensity of the rain and the length of the preceding dry weather period. Conversely, conductivity decrease during each rain event implying, that rain water acts as a dilution factor. The behaviour of COD and total nitrogen differ markedly due to their partitioning between the dissolved (total nitrogen) and particulate phases (COD). Daily pollutant fluxes allow a global comprehension and monitoring of the sewer system. Important COD fluxes during a rain event preceded by a long dry weather period highlight the importance of erosion of sedimentary deposits in the sewerage network. During these events, important fluxes are discharged into receiving water leading to the question of the impact on aquatic life. Generally, these results highlight the potential of online monitoring to better understand the behaviour of the sewer network on long or short time scales. This could be a useful tool to manage wastewater treatment.